Description of Anxiety in Facing Menarches in Grade V Students of Public Elementary School Sumput, East Java - Lestari, Nandi Rahma Dita; Maemonah, Siti; Widarti, Luluk; Cahyono, Bagus Dwi (Prodi keperawatan sidoarjo, politeknik kesehatan kemenkes surabaya indonesia, 2024)
Anxiety in facing menarche is one of the problems that is often experienced by young women. This condition can cause a decrease in pain threshold, exacerbate menstrual pain, and has the potential to become physical and emotional disturbances. Young women in Indonesia, including in Sidoarjo Regency, also face similar challenges. Lack of experience, information, and understanding about menarche is a factor causing high levels of anxiety in young women. This situation has an impact on academic achievement and can lead to depression . Study This aim to know the description of anxiety in facing menarche on fifth grade students at SD Negeri Sumput. Study This done for prevent happening anxiety in adolescents daughter moment will experience menarche. Study This use method descriptive with collect data through statement structured Revised Children's Manifest Anxiety Scale (RCMAS). Study This conducted at Sumput Public Elementary School in the month March 2023. Subject study This is female student class V SD Negeri Sumput who have not experience menarche which numbered 42 female students. Research results This show percentage level experienced anxiety students who don't experience worry ie 66.7% and students who experience worry namely 33.3%. According to researcher students who don't experience worry because they Already many earn information about menarche through a number of source information that is through electronic media, print media and direct media so that There is readiness for students in face menarche. From the results study the can concluded that female student class V SD Negeri Sumput part big female student class V SD Negeri Sumput No experience worry in face menarche.